Memory as burden and liberation : Germans and their Nazi past (1945-2010) - Wolff-Powęska, Anna 1941- (Geschichte - Erinnerung - Politik, 2015)
Mnemosyne : Mother of the Muses -- Between the end and the beginning -- Divided nation, divided memory -- The Berlin Republic : a marathon of memory -- Days of Remembrance